Diagnostically significant dysplastic feature identification as a tool for managing connective tissue risks in sports medicine - M. V. Sankova; V. N. Nikolenko (Спортивная медицина: наука и практика, 2023)
Aim: to identificate the diagnostically significant signs of connective tissue dysplasia, detection of which will allow adequate sports activity selection, injury prevention and effective rehabilitation.Materials and methods: clinical-somatometric examination of 117 persons aged 18 to 49 years (35.14 ± 5.63 years) with recurrent musculoskeletal injuries occurred during habitual physical training was carried out. Corresponding subgroups were formed by age and gender. Ranked by significance clinic-morphological dysplastic features, identified by T.I. Kadurina and L.N. Abbakumova (2008), were used to assess the mesenchymal tissue state. The control group, comparable to the main group by age and sex, was represented by 36 healthy young people.Results: persons with a predisposition to musculoskeletal injuries have a high dysplastic sign incidence. It was proved that clinically significant of them are moderate to high degree myopia, gothic palate, excessively soft auricles, “crunch” during movements in the temporomandibular joint, pathological spine kyphosis, joint hypermobility, chest deformities, O- and X-shaped legs and varicose lower limbs. Clinically significant markers of connective tissue dysplasia were found to be modified with age and to have characteristic gender features.Conclusions: the study results have particular importance for injury-free physical activity and medical-biological support for sports activities.